Contribution to the knowledge of the genus Dendarus Dejean, 1821 (Coleoptera: Tenebrionidae: Blaptinae: Dendarini) from Iran, Turkmenistan and some adjacent territories - Nabozhenko, Maxim V.; Poggi, Roberto (Zootaxa, 2022)
The taxonomic review of the genus Dendarus Dejean, 1821 from Iran and Turkmenistan is given. In total, five species are distributed in Iran and four species in South Turkmenistan; three species occur in both countries. The new species D. matthewsi sp. n. is described from Iran and compared with D. simplex Seidlitz, 1893. One taxon is resurrected from a synonymy with D. transcaspicus: D. vagabundus sp. resurr. As a result, one Afghan subspecies of D. transcaspicus belongs to another species: D. vagabundus afghanicus Kaszab, 1973. The following new synonymy is proposed: Dendarus vagabundus vagabundus Reitter, 1904 = D. transcaspicus medvedevi Kaszab, 1973, syn. n. Lectotypes of Dendarus armeniacus Baudi di Selve, 1876 and D. leonhardi Schuster, 1940 are designated. The following erroneous interpretations of Iranian and Turkmenian species are indicated: D. vagabundus = D. armeniacus sensu G. Medvedev = D. transcaspicus sensu Kaszab; D. armeniacus = D. simplex sensu G. Medvedev. New distribution data are given: D. armeniacus—N Iran (excluded from faunistic lists of Armenia, Afghanistan, Turkmenistan and Turkey); D. crenulatus (Ménétriés, 1832)—Turkey, Transcaucasia, the North Caucasus (Russia: Dagestan, Chechen Republic), N Iran, Turkmenistan (new record for the country); D. leonhardi—NE Iran, S Turkmenistan; D. matthewsi Nabozhenko sp. n.—W Iran (Zagros); D. transcaspicus Brancsik, 1899—S Turkmenistan (Kopetdag); D. vagabundus vagabundus Reitter, 1904—N Iran, S Turkmenistan (Kopetdag). Two species must be excluded from Iranian faunistic list: D. simplex—Turkey, Syria, Iraq; D. extensus (Faldermann, 1837)—Georgia, Armenia, W Azerbaijan, Turkey (new record for the country). Well-illustrated keys to males and females of Iranian and Turkmenian species of the genus are given.